Influence of Sociodemographic Factors in Hematological Parameters during Treatment of Chronic Hepatitis C. - Cunha, Elza Cristina Miranda da; Farias, Bruna Brandão; Carvalho, Natália Xavier; Viegas, Indiara; Santos, Andréia Rosa dos; Ribeiro, William Silva; Mola, Christian Loret de; Nader, Lysandro Alsina; Ghisleni, Gabriele (International Journal of Innovative Research in Medical Science, 2019)
Introduction: Adverse effects of peginterferon/ribavirin therapy and sociodemographic factors are known to modify hematological parameters. The present study was aimed to evaluate the impact of sociodemographic characteristics on laboratorial blood profile during treatment of Chronic Hepatitis C (CHC). Method: This is a Cohort of 136 patients with CHC in treatment with peginterferon/ribavirin. Sociodemographic and laboratorial profile were collected in the baseline, 4th and 12th weeks of treatment. Results: The mean age of patients was 53±11.7 years, 78 (57.4%) were men, 119 (87.5%) were Caucasian. Hemoglobin levels decreased along the treatment from baseline (14.3 ±1.7 g/dL) to 4th (12.0 ±1.8 g/dL) and 12th (11.5 ±1.6 g/dL; p=0.001). Leukocytes values also decreased from baseline to 4th and 12th weeks of treatment (6805.6 ±6574.3/mm3; 3827.6 ±1650.3/mm3 and 3541 ±2056/mm3, respectively; p=0.001), as well as platelets values (175168.06 ±60846.7mm3, 138612.06 ±59356.6/mm3, and 127279.1 ±56333.6/mm3, respectively; p=0.001). Men had greater values of hemoglobin along treatment (p=0.001), while older (p=0.012) and non-Caucasian patients (p=0.008) have lower values. Platelets levels were reduced in older (p=0.007) and men patients (p=0.001) along treatment. Conclusion: social factors as sex, age, and ethnicity, showed greater impact on hematological variables during CHC treatment, revealing an important point to be considered since may influence the management of treatment.